Case report on low dose of Cilnidipine: A fourth-generation calcium channel blocker-induced gingival overgrowth - Sameera Gopinath; Vadakkedath Venugopal Harishkumar; Vediyera Chandroth Santhosh; Sreekanth Puthalath (Journal of Indian Society of Periodontology, 2019)
Drug-induced gingival overgrowth is a frequently observed adverse effect of antihypertensive drug calcium channel blockers (CCBs). Gingival enlargements are more common with the dihydropyridine class of CCBs. The fourth-generation dihydropyridine CCB Cilnidipine was introduced in 1995 and is used as an antihypertensive agent for patients in the Indian subcontinent. This is the first report in literature to document an isolated case of generalized gingival overgrowth induced by the long-term use of low dose of cilnidipine in an elderly female patient who is under antihypertensive therapy. Gingival overgrowth is an adverse drug reaction of new-generation CCB Cilnidipine when administered even as low-dose antihypertensive therapy agent. Physicians and dentists should identify such late changes in susceptible individuals.